Study of Properties of Medical Compression Fabrics (Journal of Fiber Bioengineering and Informatics, 2018)
Compression garments apply pressure to the body to provide health benefits, such as increasing theblood circulation, shaping the body and supporting healing after medical procedures. Fabrics used forcompression garments are elastic, and the amount of fabric stretching and the ability of maintaining thestretching force are directly related to the compression effectiveness. However, there is currently littleinformation about the fabric and its mechanical properties, and there is a demand from compressiongarment manufacturers to better understand the fabric properties and their serviceability. This paperstudied the physical and mechanical properties of 4 Nylon/Spandex knitted fabrics as commercialmedical compression garments. In particular, fabric elasticity and bursting strength were examinedto demonstrate the applicability of the fabrics for providing satisfactory compression. It was observedthat the compression garment fabrics had an open knitted structure with stable dimensions, and Spandexwas only present in the wale direction. Tensile assessment revealed that the compression fabrics werestrong and their breaking extension was well beyond 200%. The fabric stretching force had a nearlinear relationship with its elongation when the fabric was stretched upto 100% extension. Afterfatigue stretching, the average immediate recovery of compression fabrics examined was more than95% and the average elastic recovery after an extended period of relaxation was at least 98%. Highfabric bursting strength and compression extension were also found. The results of fabric physicaland mechanical properties from this study are very important for understanding whether a fabric issuitable for engineering compression garments, and also for estimating the required compression forcefor designing an individualised compression garments with the medical compression fabrics.
Keywords: Compression Garment; Bursting Strength; Stress Relaxation; Elasticity; Fabric